Assessment of the yield and physico-chemical properties of sodium alginate extracted from Sagassum species. - Cusay, Jenelyn Facto
Philippine is very rich in brown seaweeds; however, utilization is limited since most of the people are not aware of the uses of these resources. Brown seaweeds specifically the genus Sargassum is known to be potential source of sodium alginate, a polysaccharide that is usually used as stabilizer, emulsifier, and thickener agent in food industry. Literature says sodium alginate can also be used as an effective feed binder for animal feeds. The percent yield, viscosity, gel strength and hardness of sodium alginate extracted from two to be identified Sargassum species were determined and compared. Results of the analysis showed that there is no significant variation in the means of yield of sodium alginate from species A abd species B. However, there are significant variation on the means of gel strength, hardness and viscosity between the two. The higher percent recovery (19.46%) abd greater viscosity (37.7 cP) were obtained from species B whereas the higher gel strength and hardness were observed from species A, 42.79558 N mm and 2.4072 N respectively. The results of the water stability test using formulated abalone diet pellets showed that sodium alginate from species A and B have good binding capacity retaining 76.30% and 77.32% of the feed respectively after 8 hours of submersion in water.